Pengaruh Good Corporate Governance terhadap Financial Distress dan Dampaknya bagi Nilai Perusahaan - Robert Jao; Fransiskus Randa; Anthony Holly; Harun Widodo (Worksheet : Jurnal Akuntansi, 2026)
The purpose of this study is to analyze the effect of good corporate governance proxied by managerial ownership, institutional ownership, and independent board of commissioners on firm value mediated by financial distress. This study uses agency theory to explain the relationship between variables. The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The data sources used are secondary data in the form of financial reports and annual reports obtained from the Indonesia Stock Exchange and the company's official website. The number of samples is 425 company data for 5 years, which were selected using the purposive sampling method. The results of the study indicate that managerial ownership, institutional ownership, and independent board of commissioners have a significant negative effect on financial distress. This study also found that managerial ownership and institutional ownership have a significant positive effect on firm value, but the independent board of commissioners has a positive but insignificant effect on firm value. In addition, it was also found that financial distress has a significant negative effect on firm value. Finally, this study found that financial distress mediates the relationship between managerial ownership, institutional ownership, and independent board of commissioners on firm value.